How stems of sorghum silage are digested - Harbers, L.H.; Schweitzer, R.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Upper and lower portions of stem from three sorghum cultivars were ensiled and then subjected to rumen fermentation. The lower stems were readily digested, whereas the upper sections were poorly utilized. Several microscopic techniques were used to help explain the difference.
Keywords: Beef; Sorghum silage; Rumen; Fermentation